К вопросу оптимизации нелинейных колебательных систем - Токарева, О.Н. (Теорія оптимальних рішень, 2006)
For the considered optimization models of nonlinear elastic dissipative dynamic systems, the key moment for the proposed algorithm that solves them is transition from a conjugate differential equation system to a vector second – type Fredholm equation and anexplicit solution to the laller by the spectral method.